Modern Approaches for the Physical Training of Young Female Basketball Players - Komotska, Oksana; Sushko, Ruslana (Physical Education Theory and Methodology, 2022)
The study purpose was to substantiate, develop and test the effectiveness of the author’s program for physical training of young female basketball players in the pre-competition period of the macrocycle preparatory stage, and to experimentally test its effectiveness. Materials and methods. The subjects were 15 young female basketball players born in 2007-2008, third year of study (1st year of study in the basic training group), members of the All-Ukrainian Youth Basketball League (AUYBL), who participated in the experimental program to improve their physical fitness. Three tests on six indicators of physical fitness were conducted. The results of a consecutive experiment for young basketball players during their training in the camp were analyzed and interpreted. Results. The author’s program for physical training of young female basketball players was developed and implemented during the training camp in order to increase their level of physical fitness and preparation for participation in the AUYBL competitions. The results of the study, which were obtained during a series of experiments, allowed to examine and analyze six indicators of physical fitness, and to substantiate the effectiveness of modern approaches to physical training of young female basketball players in the pre-competition period of the macrocycle preparatory stage. They were based on the minimization of additional workload and focused concentration of female athletes on the quality of specific exercises in a limited period. Conclusions. The analysis of the results, the indicators of physical fitness of young female basketball players, allows to state that the use of the author’s program for physical training makes it possible to record the improvement of physical fitness on tests that have speed-strength and strength orientation, namely: high jump, long jump, run for 40 s, flexion-extension of the arms at thrust lying for 30 s. According to the indicators of speed tests (20 m run and 60 m sprint), no statistically significant differences were recorded, with a tendency to their improvement.